1997
DOI: 10.1289/ehp.97105s3577
|View full text |Cite
|
Sign up to set email alerts
|

During development, 17alpha-estradiol is a potent estrogen and carcinogen.

Abstract: 577-581 (1997)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…A limitation of this study was the number of doses used, but there appeared to be a pattern of increased CV-tract tumors with the higher doses. These data strongly support the theory that relatively weak estrogens can induce tumors in mice when exposure occurs during a critical period of development ( Hajek et al 1997 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A limitation of this study was the number of doses used, but there appeared to be a pattern of increased CV-tract tumors with the higher doses. These data strongly support the theory that relatively weak estrogens can induce tumors in mice when exposure occurs during a critical period of development ( Hajek et al 1997 ).…”
Section: Discussionsupporting
confidence: 87%
“…The neonatal mouse model has been extensively studied for more than four decades and has proven extremely valuable in assessing human in utero exposure to DES. The defined period for causation of genital tract tumors by natural (17α-estradiol and E 2 ) and synthetic (e.g., DES) estrogens occurs during the development of the reproductive tract in both humans and rodents ( Hajek et al 1997 ). The use of the neonatal mouse model was necessary because, unlike findings in adult-treated rodents ( Liehr et al 1986 ), an apparent correlation between estrogenicity and carcinogenicity exists in neonatally treated rodents ( Newbold et al 1990 , 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the purpose of this study was to determine the severity of ageassociated OA in genetically heterogeneous male mice and determine if the severity of ageassociated OA was reduced in mice treated with selected agents in the ITP study that were found to increase life span. Findings were compared to Ames dwarf mice, which are deficient in growth hormone and are genetically long-lived 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, αE2 also produces appreciable uterotrophic effect in OVX rodents, as we show here in agreement with others. 18,19 Therefore, confinement of the action of this estrogen into the brain is highly desirable to avoid unwanted hormonal impact on the periphery. This is even more pressing in the context of translational research, as most estrogen-responsive maladies require long-term treatments that bring about critical consideration for safety and efficacy, highlighting thereby the need for brain-selective neurotherapy when proposing the use of αE2 as a preventative and/or curative agent.…”
mentioning
confidence: 99%